Analysis of the Clinicopathologic Characteristics and Prognosis of Head and Neck Lymphoma - Shufang Yan; Jiajia Ma; Meihong Yang; Bo Liu; Sijing Li; Liuqing Yang; Qian Zhang; Xinxia Li (Analytical Cellular Pathology)
Statistical reports on non-Hodgkin’s lymphoma (NHL) of the head and neck combining clinical medicine with pathology are rare. To provide a basis for prognosis prediction and individualized treatment, we will investigate the clinicopathologic characteristics and prognosis of lymphoma in the head and neck region. Four hundred sixty-one patients with NHL in the head and neck region diagnosed through histological biopsy were retrospectively analyzed. Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) were performed in all cases to evaluate the genetic status and protein expression levels. Patients were followed up by telephone. The prevalence rate of primary extranodal NHL (PENHL) in the head and neck region was 44.62% (166/372). The incidence of extranodal lymphoma accounted for 36.66% (169/461) of all head and neck lymphomas. Among the cases of PENHL of the head and neck, diffuse large B-cell lymphoma (DLBCL) (60/76, 78.95%) and extranodal NK/T-cell lymphoma, nasal type (ENKTCL) (21/24, 87.5%) were the most common subtypes originating from B-cell lymphoma (BCL) and T-cell lymphoma (TCL), respectively. The most common sites of nodal and extranodal onset were neck lymph nodes and the gastrointestinal tract, respectively. The most common and primary locations of BCL and TCL were the tonsils and nasal cavity, respectively. The 3-year survival rates of PENHL, ENKTCL, and DLBCL of the head and neck were 42%, 28.57%, and 41.67%, respectively, and the 5-year survival rates were 24%, 19.05%, and 20%, respectively. Survival analysis showed that male sex was a risk factor (HR=5.421; 95% CI, 1.164-25.267; p<0.05) and that comprehensive treatment was a protective factor (HR=0.117; 95% CI, 0.025-0.545; p<0.05) against extranodal DLBCL in the head and neck region. Bone marrow involvement was a risk factor for PENHL of the head and neck (HR=5.072; 95% CI, 1.17-21.991; p<0.05). The purpose of this review is to show that PENHL of the head and neck with high incidence deserves more attention, and a model of multidisciplinary diagnosis and treatment should be adopted.